EFEK PENAMBAHAN TEPUNG SAGU TERHADAP KARAKTERISTIK KERUPUK IKAN DENCIS - Mulyana; Angraeni, Lia; Puteri, Nafisah Eka (Jurnal Agroindustri Pangan, 2025)
This study aims to evaluate the impact of sago flour addition on the physicochemical and organoleptic characteristics of dencis fish crackers (Decapterus macrosoma). The crackers were produced with varying concentrations of sago flour at 0% (B1), 20% (B2), 40% (B3), and 60% (B4), employing an experimental approach based on a Completely Randomized Design (CRD). The analysis results indicated that the water content of the crackers increased with higher concentrations of sago flour, while the ash content exhibited a decreasing trend. Additionally, the fat content increased; however, both the swelling volume and oil absorption capacity decreased. The hedonic test results revealed that panelists exhibited a preference for crackers made exclusively from tapioca flour (B1), with a notable decline in preference for color, taste, and crispiness as the concentration of sago flour increased. These findings suggest that utilizing sago flour in reduced quantities or in combination with other flours may enhance the quality of the crackers. It is recommended that future research explore alternative formulations for the crackers and investigate different cooking methods to achieve optimal gelatinization of sago starch.